Inhibitory effects of bromoindoles on Escherichia coli O157:H7 biofilms - Jeon, Hyejin; Boya, Bharath Reddy; Kim, Gyuwon; Lee, Jin-Hyung; Lee, Jintae (Biotechnology and bioprocess engineering, 2024)
Enterohemorrhagic Escherichia coli O157:H7 (EHEC) is responsible for outbreaks of hemorrhagic colitis worldwide, but no effective therapy exists for EHEC infections. EHEC readily forms antimicrobial-tolerant biofilms on various biotic and abiotic surfaces. Here, we investigated the antimicrobial and antibiofilm abilities of 16 halogenated (fluoro-, chloro-, bromo-, or iodo-) indoles and indole against a pathogenic EHEC strain . Antibiofilm activities followed the order chloroindoles > bromoindoles > indole > fluoroindoles. For example, the minimum inhibitory concentrations (MICs) of 4-bromoindole and 5-bromoindole were 100 and 200 μg/mL, respectively, and at 20 μg/mL, they both inhibited EHEC biofilm formation by more than 61% without affecting planktonic cell growth. However, at concentrations greater than their MICs, both showed bactericidal activity. Antibiofilm effects were confirmed by scanning electron microscopy. Both 4-bromoindole and 5-bromoindole reduced swimming and swarming motility and curli formation, which are important factors for EHEC biofilm formation. Furthermore, quantitative structure–activity relationship analysis demonstrated that halogenation of indole with chlorine, bromine, or iodine at positions C-4 or C-5 promotes antimicrobial activity but that substitution at C-7 is detrimental. The study shows that halogenated indoles, particularly bromoindoles, have potential use as antimicrobial and antibiofilm therapies against EHEC.